Participation of adult patients in healthcare - Šulistová, Radka; Stasková, Věra; Kaas, Jiří; Kimmer, David; Treslova, Marie; Olišarová, Věra; Filausová, Drahomíra (Neuro-endocrinology letters, 2016)
In this study, the question of health literacy in adult patient population in the Czech Republic is explored in the context of healthcare, particularly in the South Bohemian Region. The study is based on the analysis of qualitative data which were collected during the first half of 2016. The study included 34 adult participants at the age range between 18 and 64 years. The study is focused on the involvement of adult patients in the process of decision making concerning the healthcare provided. The views of this sort of problems were recorded by the technique of semi-structured dialogues. The study results have suggested that adult individuals accept the healthcare provided by doctors or nurses prevailingly with trust. In addition, they have shown that in the sphere of health education, the adults lack the knowledge of the right for information about the individual's health condition and information about the service provided by the health insurance agency. It is regarded as desirable to deal with the topic of health literacy of adult population, particularly in the area of internet counselling and telemedicine, and to develop the space for information sharing between the doctor and nurse on one side and the patient on the other.
Keywords: mladý dospělý; Patient Participation; Adult; Adolescent; Young Adult; zapojení pacienta; lidé středního věku; mladiství; Qualitative Research; Czech Republic; ženské pohlaví; lidé; Česká republika; mužské pohlaví; zdravotní gramotnost; dospělí; Humans; Health Literacy; Patient Acceptance of Health Care; Female; Middle Aged; kvalitativní výzkum; Male; pacientův souhlas se zdravotní péčí